Evaluation, fabrication and dynamic performance regulation of green EMI-shielding materials with low reflectivity: A review. (15th March 2022) - Jia, Xichen; Li, Yang; Shen, Bin; Zheng, Wenge
Abstract: Electromagnetic interference (EMI) shielding materials have been employed to diminish environmental electromagnetic radiations by reflecting and absorbing transmitted EM wave. However, most of the researchers focus on improving the electrical conductivity of the materials, which is conducive to improving EMI shielding performance, but it will also increase the EM reflection, leading to the inevitable secondary EM pollution. Therefore, it is momentous to develop novel green EMI shielding materials with low reflectivity for environmentally friendly applications. In this review, we introduce the evaluation methods and influence factors of low-reflectivity green EMI shielding materials. Subsequently, the recently reported fabrication approaches as well as the corresponding EMI shielding performance and mechanism in regards to the low-reflectivity green EMI shields are summarized, and the ways for dynamic performance regulation of recently reported EMI shielding materials are concluded as well. Finally, the extant challenges of design and fabrication for low-reflectivity EMI shielding materials needed to be concerned are proposed, and the research tendency of low-reflectivity EMI shielding materials are prospected. Graphical abstract: Image 1